YOUTH MUTICULTURAL COMMUNITY BASE ON LOCAL CULTURE OF MANGGARAI AS THE EFFORT TO FIGHT AGAINST VIOLENCE, RADICALISM AND TERORISM - Fransiska Widyawati; Yohanes Albino (Unika Santu Paulus Ruteng, 2020)
Violence, radicalism and terrorism have become a real threat to the human community today. The culprit can be anyone, including young people. Many young people have been no longer open, dialogic and multicultural in society. Many of them have been exposed to radicalisme and have a narrow ideology. This research argues that young people need to be helped to learn to live together with other young people, in open and multicultural and multi-religious communities. Therefore, the research develops a multicultural community model of young people based on the local context and culture of the Manggarai people. The model is names as Nai Ca Anggit Tuka Ca Léléng Communitty. The strength of the community is one its unity, harmony and brother/sisterhood values. This multicultural community of young people becomes a forum where young people from various religious backgrounds, ethnicities, races, regions, etc. gather and work together to promote a world and life that is non-violent, open and dialogical. By joining and participating on this community, young people want to show their roots in local communities, to be involved in the preservation of local culture and to involve local people in the struggle and action to ward off the danger of violence, radicalism and terrorism.